Students Perception of Using Google Translate in Learning English - Nurhayati, Nurhayati; Lahete, Inke (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study is to determine students' perceptions of the use of Google Translate in English learning, in terms of absorption, understanding, and evaluation. This study used quantitative methods with descriptive design analysis. The average score is used to answer the research question. The instrument used in this study was a questionnaire. Responded to this study were grade 7 students in one of the junior high schools in Airmadidi North Minahasa totaling 173 students. The results of the analysis showed that students agreed that absorption factors influenced students' perceptions of the use of Google Translate in learning English. Students agree that comprehension factors influence students' perceptions of using Google Translate in English language learning. Students strongly agree that evaluation factors influence students' perceptions of the use of Google Translate in English language learning. So, it can be concluded that students' perception of the use of Google Translate is positive judging from the factors that affect the use of Google Translate. However, students should use Google Translate as a useful additional tool to understand English Lessons better